2006
DOI: 10.1021/la060661v
|View full text |Cite
|
Sign up to set email alerts
|

Green Fluorescent Protein-ExpressingEscherichiacolias a Model System for Investigating the Antimicrobial Activities of Silver Nanoparticles

Abstract: Recombinant Escherichia coli (E. coli) bacteria expressing green fluorescent protein (GFP) was used as a model system to investigate the antimicrobial activities of Ag nanoparticles (NPs). A convenient in situ method of Ag NP synthesis using sodium borohydride, in the bacterial growth medium, was developed to produce preformed NPs for the study. Fluorescence spectroscopic and microscopic techniques allowed rapid detection of time-dependent changes in bacterial growth as well as fluorescence characteristics in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
240
1
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 425 publications
(265 citation statements)
references
References 22 publications
13
240
1
11
Order By: Relevance
“…For treatment with silver nitrate, a low molecular weight central region was formed within the cells as a defense mechanism, whereas for treatment with nanoparticles, no such phenomenon was observed, although the nanoparticles were found to penetrate through the cell wall. With a detailed study of DNA/protein migration profiles Gogoi et al [32] demonstrated that silver nanoparticles have no direct effect on either cellular DNA or protein, although the silver nanoparticles were more efficient bactericidal agent compared to the silver ions [33]. For E. coli (ATCC 10536) and S. aureus (ML 422), silver nanoparticles demonstrated greater bactericidal efficiency compared to penicillin [37].…”
Section: Resultsmentioning
confidence: 99%
“…For treatment with silver nitrate, a low molecular weight central region was formed within the cells as a defense mechanism, whereas for treatment with nanoparticles, no such phenomenon was observed, although the nanoparticles were found to penetrate through the cell wall. With a detailed study of DNA/protein migration profiles Gogoi et al [32] demonstrated that silver nanoparticles have no direct effect on either cellular DNA or protein, although the silver nanoparticles were more efficient bactericidal agent compared to the silver ions [33]. For E. coli (ATCC 10536) and S. aureus (ML 422), silver nanoparticles demonstrated greater bactericidal efficiency compared to penicillin [37].…”
Section: Resultsmentioning
confidence: 99%
“…One of the probable mechanism is that silver nanoparticles attach to the surface of the cell membrane, the respiratory function and permeability of the bacterial cells become unstable (Kvitek et al 2008). According to Gogoi (Gogoi et al 2006), the negatively charged cell surface of E. coli is easily dislodged by Ag ? ions thus interrupting metabolic activity and subsequently leading to The different zone size formed by adding (50 and 100 ll) of neem extract and AgNP after streaking E. coli on EMB plate denaturation of protein and cell death (Pal et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the abundance of sulfurcontaining proteins on the bacterial cell membrane, silver nanoparticles can react with sulfur-containing amino acids inside or outside the cell membrane, which in turn affects bacterial cell viability. It was also suggested that silver ions (particularly Ag + ) released from silver nanoparticles can interact with phosphorus moieties in DNA, resulting in inactivation of DNA replication, or reacting with sulfurcontaining proteins, leading to the inhibition of enzyme functions which results in loss of cell viability and eventually resulting in cell death [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%